Herbert T. Kalmus papers - Kalmus, Herbert T. (Herbert Thomas), 1881-1963.
Correspondence and financial records chiefly concerning Kalmus's personal affairs and finances. Also includes business records concerning Technicolor, Inc., Technicolor Motion Picture Corporation, and Technicolor Limited; writings including drafts of his memoir Mr. Technicolor; appointment books; printed matter; photographs; and other papers. Subjects include his art collection, Massachusetts Institute of Technology, the Society of Motion Picture and Television Engineers, and the Stanford Research Institute. Correspondents include Terence Cooke, Alice R. Gallagher, Florence Harris, J. Francis A. McIntyre, and Francis Spellman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Chemical engineer, inventor, and businessman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Cooke, Terence, -- 1921-1983 -- Correspondence; Gallagher, Alice R. -- Correspondence; Harris, Florence -- Correspondence; Kalmus, Herbert T. -- 1881-1963 -- Art collections; McIntyre, J. Francis A. -- 1886-1979 -- Correspondence; Spellman, Francis, -- 1889-1967 -- Correspondence; Massachusetts Institute of Technology; Society of Motion Picture and Television Engineers; Stanford Research Institute; Technicolor, Inc; Businessmen; Chemical engineers; Inventors